HOMEOSTATC PROLIFERATION AS A BASIS FOR THE INEVITABLE FORMATION OF TOTAL IMMUNODEFICIENCY - V. A. Kozlov (Медицинская иммунология, 2014)
Numerous literature data indicate to gradual, but steady ageependent decrease of immunological reactivity in human organism, manifesting as a reduced ability to develop specific immune response, both of cellular and humoral type. Such negative trends result into increased proposition and frequency of various diseases, including cancer and autoimmune disorders. Finally, an age-associated immunodeficiency is developed even in normal organism, without clear background of specific disorders. The multicomponent mechanisms of such deficiency are not yet fully clarified. One may assume that, among these potentially leading mechanisms, a homeostatic proliferation may be of sufficient importance. This type of cell growth is shown to accompany any negative effects on the numbers of lymphocytes in the body. It manifests as a reduced ability of lymphocytes to recognize foreign antigens associated with a background increase of self-reactive cells.